Cover Image. (20th May 2020) - Grandidier, Jonathan; Kirk, Alexander P.; Jahelka, Phillip; Stevens, Margaret A.; Gogna, Pawan K.; Crisp, David; Osowski, Mark L.; Vandervelde, Thomas E.; Atwater, Harry A.; Cutts, James A.
Abstract : The cover image is based on the EU PVSEC Paper Photovoltaic operation in the lower atmosphere and at the surface of Venus by Jonathan Grandidier at al., https://doi.org/10.1002/pip.3214 .